A Systemic Analysis of Land Markets and Land Institutions in West African Cities Rules and Practices - The Case of Bamako, Mali - Durand-Lasserve, Alain (The World Bank, 2013)
This paper presents a new type of land market analysis relevant to cities with plural tenure systems as in West Africa. The methodology hinges on a systemic analysis of land delivery channels, which helps to show how land is initially made available for circulation, how tenure can be formalized incrementally, and the different means whereby households can access land. The analysis is applied to the area of Bamako in Mali, where information was collected through (i) interviews with key informants, (ii) a literature review on land policies, public allocations, and customary transfers of land, (iii) a press review on land disputes, and (iv) a survey of more than 1,600 land transfers of un-built plots that occurred between 2009 and 2012. The analysis finds that land is mostly accessed through an informal customary channel, whereby peri-urban land is transformed from agricultural to residential use, and through a public channel, which involves the administrative allocation of residential plots to households. The integrated analysis of land markets and land institutions stresses the complexity of procedures and the extra-legality of practices that strongly affect the functioning of formal and informal markets and make access to land costly and insecure, with negative social, economic, and environmental impacts over the long term